Exploring Sleep Quality in Postoperative Recovery Following Anterior Discectomy for Cervical Herniated Nucleus Pulposus Surgery - Bima Abiyasa; Raksa Manggala (International Journal on ObGyn and Health Sciences, 2023)
Cervical Herniated Nucleus Pulposus (HNP) surgery, particularly using the anterior discectomy method, is a common intervention to address the debilitating symptoms associated with disc herniation in the cervical spine. While the immediate goals of surgery include pain relief and neurological improvement, the impact on sleep quality remains a relatively underexplored aspect. This research aims to investigate the differences in sleep quality among patients undergoing anterior discectomy for cervical HNP surgery, offering insights into the broader implications for postoperative recovery. A prospective cohort study was conducted, involving patients diagnosed with cervical HNP scheduled for anterior discectomy. Sleep quality assessments were performed preoperatively and at defined intervals postoperatively using validated tools such as the Pittsburgh Sleep Quality Index (PSQI) and subjective sleep diaries. Surgical procedures followed established protocols, and data were analyzed using statistical methods to identify significant differences in sleep metrics. The analysis revealed statistically significant improvements in various sleep quality metrics postoperatively. Participants experienced reduced sleep latency, increased sleep duration, and diminished disturbances during the night. The overall perceived sleep quality showed a notable enhancement. Short-term improvements were particularly pronounced, though some measures exhibited a gradual return toward baseline levels over time. Subgroup analyses highlighted variations in sleep outcomes based on factors such as age, preoperative pain levels, and surgical complications.